Patient and Family Engagement: The Secret Behind Quality Healthcare Services (Literature Review) - Ahyar Wahyudi; Iwan Trihapsoro; Listyo Yuwanto; Ratna Indrawati; Hisnindarsyah; Buyung Nazeli (East Asian Journal of Multidisciplinary Research, 2023)
World Patient Safety Day 2023 underscores the significance of patient engagement, aligning with the principles advocated by Don Berwick. This article underscores the importance of involving patients and their families in healthcare services, with a focus on effective communication, cultural differences, varied levels of patient engagement, access to information, privacy, and resource constraints. The concept of "Person-Centered Care" epitomizes the effort to engage patients in making decisions about their care, supported by theories and expert models such as the Patient Engagement Model and the Shared DecisionMaking Approach. To overcome the barriers to patient engagement, it is essential to provide training for medical staff, foster cultural awareness, ensure secure technology, and allocate resources judiciously. These measures will enhance the quality of care, safety, satisfaction, emotional support, and the efficiency of long-term care management. Patient and family engagement forms the cornerstone of quality and holistic healthcare in an increasingly complex healthcare landscape.